Diagnostic Impact of Monitoring Visual Evoked Potentials to Prevent Visual Complications During Endovascular Treatment for Intracranial Aneurysm - Nakagawa, Ichiro; Park, HunSoo; Kotsugi, Masashi; Yokoyama, Shohei; Omoto, Kouji; Myochin, Kaoru; Takeshima, Yasuhiro; Matsuda, Ryosuke; Nishimura, Fumihiko; Yamada, Shuichi; Takatani, Tsunenori; Nakase, Hiroyuki (Frontiers in Neurology, 2022)
Introduction The present study aimed to determine the incidence of intraprocedural visual-evoked potential (VEP) changes and to identify correlations with intraprocedural ischemic complications during endovascular treatment in patients with intracranial aneurysm related to visual function. Methods This study analyzed data from 104 consecutive patients who underwent endovascular coil embolization to treat intracranial aneurysms related to visual function under VEP and transcranial motor evoked potential (MEP) monitoring. We analyzed associations between significant changes in MEP and VEP, defined as a >50% decrease in amplitude, and both intraprocedural complications and postoperative neurological deficits. Factors associated with postoperative neurological deficits were also assessed. Results Treated aneurysms were predominantly located in the internal carotid artery (95%). Five (5%) were located in the posterior cerebral artery (PCA). Significant decreases in intraprocedural VEP occurred in four patients (4%), although one of those four patients did not show concomitant MEP decreases during procedures. Immediate salvage procedures avoided postoperative visual disturbances. All VEP decreases were transient and not associated with postoperative visual impairment. One of three cases who underwent intraoperative balloon occlusion test showed tolerance to balloon occlusion of the proximal PCA under VEP assessment; parent artery occlusion was performed without postoperative visual disturbance in that case. Conclusion Although significant VEP decreases occurred 4% during neuro-endovascular aneurysm treatment related to visual function, intraprocedural VEP monitoring identifies ischemic changes associated with visual pathways and facilitates prompt initiation of salvage procedures.